Comparative Study of Syndrome of Inappropriate Antidiuretic Hormone Secretion and Cerebral Salt Wasting Syndrome in Stroke Patients - Chowdhury, Md. Mubinul Huq; Md. Hassanuzzaman; Touhidur Rahman; Farhana Moslehuddin; Mohammad Rifat Kamal; Riyadh Muhammad Marzuk; Shagor Deb Tapu; Syed Arif Uddin; Samee M Adnan; Kamrul Hassan; et al. (Bangladesh Journal of Neuroscience, 2026)
Background: Hyponatremia is a common finding after stroke and can be caused by either cerebral salt-wasting syndrome (CSWS) or syndrome of inappropriate antidiuretic hormone secretion (SIADH). Distinguishing between these two entities can be difficult because they have similar manifestations, including hyponatremia, serum hypoosmolality, and high urine osmolality. Objectives: The study aimed to determine the differences in frequency, clinical profile, and outcome of CSWS and SIADH among stroke patients with hyponatremia admitted to a Neurology department of a tertiary teaching hospital in Bangladesh. Methods: One hundred and three patients with stroke having hyponatremia from the Department ofNeurology of Chittagong Medical College Hospital were included in the study. Based on the clinical and laboratory parameters the type of hyponatremia (CSWS or SIADH) was determined. In-hospital and 30-day outcome were compared between patients with CSWS and SIADH. Results: Out of 103 patients, 65 (63.1%) had SIADH and 38 (36.9%) had CSWS. The proportion of patients with ischemic stroke was higher in the SIADH group than in the CSW group (90.8% versus 60.5%, p<0.001). The median (IQR) GCS was comparatively lower in patients with CSWS [10 (8-12)] than the patients with SIADH [11 (9-13)] (p=0.044). The median (IQR) stay in the hospital for the patients with SIADH was shorter [5.0 (4.0-9.0) days] than the in the patients with CSWS [8.0 (6.8-12.3) days] (p=0.001). At 30 days, out of 97 assessed patients, the mortality rate was 6.6% and 38.9%, respectively, in patients with SIADH and CSWS (p<0.001). Patients with CSWS were 8.67 times more likely to die within 30-days than the patients who had hyponatremia due to SIADH (OR: 8.67, 95% CI:2.22-33.75, p=0.002). Conclusions: Hyponatremia have impact on stroke outcome, mainly when caused by CSWS. Therefore, it requires close monitoring, accurate diagnosis, and prompt treatment.